Malaysian: public administration: for beginners / Asmidar Lokman … [et al.] - Lokman, Asmidar; Yaakub, Ahmad Faiz; Abdul Razak, Shahidah; Ab. Rahman, Farah Adilla
All the authors are lecturers of the Faculty of Administrative Science and Policy Studies of Universiti Teknologi MARA. All possess tertiary education background in Public Administration or Public Management with more than 10 to 20 years of field experience. That said, this book is written with the students in mind. For many years, it has been a challenge for the students to find a book that specifically covers the syllabus of this subject. Therefore, each author writes specific topic to ensure the syllabus is well covered. In doing so, this book takes a general approach with a specific focus on Malaysian public service. It covers the important components in the study of public administration in Malaysia namely: (i) The Definition and Concept of Public Administration and its Components i.e. Public Organisations, (ii) Public Administration Activities such as Public Finance, Personnel Administration and Public Policy, and (iii) Ethical Perspective of Public Administration. Many have contributed to this book. Firstly, we would like to express our gratitude to the editors, Dr. Asri Salleh and Dr. Nadrawina Isnin who had diligently reviewed the work, time and again offering and sharing insights and key points to be included in the chapters. Our appreciation also goes to Encik Shahril Eashak Ismail for providing the illustrations. Our special thanks also go to the Dean of the Faculty of Administrative Science and Policy Studies, UiTM as well as UiTM Press for their strong support in materialising this book.